Equitable remedy : injunction - Wong, Yuen Hwa (2006)
Damages are always the usual remedy when there is a breach of contract. However, due to the limited effectiveness of the remedy of damages in some cases, it caused the development of equity, and subsequently equitable remedies. Injunction is one of the equitable remedies and it is regarded as extraordinary. It is made available only in limited circumstances. Threfore, this master project intends to identify what circumstances, which is limited, that injunction will be available to the parties in a building contract. This project is carried out mainly through documentary analysis of law journals, such as Malayan Law Journal, Singapore Law Report, Building Law Report, etc. Due to time constraint, questionnaire survey or interview is not carried out. Results show that there are 11 circumstances in which the injunctions (prohibitory, mandatory and Mareva injunctions) will be available to the parties and 4 circumstances in which injunction would not be available to the parties in a building contract (as provided in Chapter 4). Rhind J in the case of Concorde Construction Co Ltd v Colgan Co Ltd [1984] 29 Build LR 120 mentioned that the judge will ordinarily grant injunction â€œas of courseâ€ in certain familiar situations which keep recurring. Since the circumstances discussed are the situations which had occur for the past few 10 years, therefore, it is hoped that it would provide a guideline to parties in a building contract when they could succeeding in applying injunction if they resort to it.